2010
DOI: 10.1073/pnas.1004785107
|View full text |Cite
|
Sign up to set email alerts
|

Defining the mechanism of polymerization in the serpinopathies

Abstract: The serpinopathies result from the ordered polymerization of mutants of members of the serine proteinase inhibitor (serpin) superfamily. These polymers are retained within the cell of synthesis where they cause a toxic gain of function. The serpinopathies are exemplified by inclusions that form with the common severe Z mutant of α 1 -antitrypsin that are associated with liver cirrhosis. There is considerable controversy as to the pathway of serpin polymerization and the structure of pathogenic polymers that ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
144
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 126 publications
(150 citation statements)
references
References 33 publications
6
144
0
Order By: Relevance
“…This antibody binds polymers formed by heating monomeric α 1 -antitrypsin, but not those formed by refolding from guanidine and urea [15]. Our NMR studies followed the polymerisation of Queen's (Lys154Asn) α 1 -antitrypsin under physiological conditions or in urea.…”
Section: Controversies On the Structure Of The Pathological Polymermentioning
confidence: 99%
See 2 more Smart Citations
“…This antibody binds polymers formed by heating monomeric α 1 -antitrypsin, but not those formed by refolding from guanidine and urea [15]. Our NMR studies followed the polymerisation of Queen's (Lys154Asn) α 1 -antitrypsin under physiological conditions or in urea.…”
Section: Controversies On the Structure Of The Pathological Polymermentioning
confidence: 99%
“…The application of heat to monomeric α 1 -antitrypsin recapitulated the 2C1 neo-epitope of polymers associated with disease [15].…”
Section: Controversies On the Structure Of The Pathological Polymermentioning
confidence: 99%
See 1 more Smart Citation
“…While denaturant can induce polymerization at concentrations that favour population of an unfolding intermediate state (I denat ) [6,20], observations indicate that there are multiple pathways favoured depending on the manner in which polymers are formed, and as a result intermediate ensembles represented by I pol and I denat could be structurally distinct [19]. In support of this, it has recently been shown that polymers produced in the presence of denaturant lack an epitope that is expressed on polymer obtained from patient samples [18,21]. Given this diversity it is unsurprising that there are currently three main models for the terminal polymer that differ from one another in fundamental respects ( Figure 1B).…”
Section: Introductionmentioning
confidence: 96%
“…During the activation to intermediate, there is a change in far-UV circular dichroic signal, intrinsic tryptophan fluorescence, the interaction with ANS (8-anilinonaphthalene-1-sulfonic acid) or bis-ANS (4,4 -dianilino-1,1 -binaphthyl-5,5 -disulfonic acid) dyes [14,17], ion mobility mass spectrum collision crosssectional area [18] and NMR cross-peaks [19]. While denaturant can induce polymerization at concentrations that favour population of an unfolding intermediate state (I denat ) [6,20], observations indicate that there are multiple pathways favoured depending on the manner in which polymers are formed, and as a result intermediate ensembles represented by I pol and I denat could be structurally distinct [19].…”
Section: Introductionmentioning
confidence: 99%